Amazigh-Sys: Intelligent system for recognition of amazigh words - Rachid Ammari; Lahbib Zenkouar (IAES International Journal of Artificial Intelligence (IJ-AI), 2021)
Amazigh-sys is an intelligent morphological analysis system for Amazigh language based on xerox’s finite-state transducer (XFST). Our system can process simultaneously five lexical units. This paper begins with the development of Amazigh lexicon (AMAlex) for attested nouns, verbs, pronouns, prepositions, and adverbs and the characteristics relating to each lemma. A set of rules are added to define the inflectional behavior and morphosyntactic links of each entry as well as the relationship between the different lexical units. The use of finite-state technology ensures the bidirectionality of our system (analysis and generation). Amazigh-sys is the first general morphological analysis system for Amazigh based on xerox finite state able to process and recognize all lexical units and ensures a high recognition rate of input words. This contribution facilitates the implementation of other applications related to the automatic processing of the Amazigh language.